Psychosocial rehabilitation experiences of the ACL reconstructed athlete - Neibert, P. J. (Journal of Athletic Training, 2012)
Context: The majority of research on the rehabilitation process, for the ACL reconstructed athlete, has focused on physical rehabilitation. There is very little research on the psychosocial aspect of the ACL reconstructed athlete`s rehabilitation experience. Objective: To explore the ACL reconstructed athlete`s psychosocial rehabilitation experiences. Further, to discover the psychosocial support mechanisms utilized during the rehabilitation process. Design: Descriptive qualitative method of inquiry with a grounded theory approach. Setting: Structured personal interviews were conducted with NCAA Division I collegiate athletes in the Midwest. Patients or Other Participants:9 NCAA Division I athletes (5 males, 4 females; 19.33 ± 1.035 years old),attending 4 different institutions in the Midwest who have completed their rehabilitation for an ACL reconstructed knee were interviewed. Data Collection and Analysis: Data was collected via recorded personal interviews. Data was analyzed through the constant comparative method of grounded theory. Data triangulation, member checking, and peer-review strategies were used to ensure trustworthiness of the data. Results: Athletes reported that their relationship with their AT was the most important psychosocial support mechanism during the rehabilitation process. Athletes viewed their AT as a psychologically stabilizing force. The ATs ability to encourage, reassure and relate to the rehabilitation process was paramount. In addition to the AT support, the athletes reported that support from the coaching staff was also an important psychosocial support mechanism. One participant reported that the lack of psychosocial support from the coaching staff was psychologically detrimental to her rehabilitation experience. These psychosocial support mechanisms were crucial in helping the athlete to deal with the psychological aspect of their rehabilitation experience. Conclusions: My findings are consistent with the psychosocial literature that illustrates the crucial role ATs/coaches play as a psychosocial support during the rehabilitation process and the importance of this relationship to athlete/patient. Future researchers should take a closer look at the perceptions of NCAA Division I coaches` role in the psychosocial support of the athlete during the rehabilitation process.